Fluid mechanics - Douglas, J F (Longman, 1995)
The book provides a comprehensive treatment of the essentials of the subject students of civil, mechanical or chemical engineering and building services or environmental engineering. It includes: start-of-chapter objectives and end-of-chapter summaries. It also includes expanded material on dimensional analysis and similarity, motion of fluid particles and streams, the energy equation and its applications, non-uniform flow in open channels, pressure transient theory, surge control, and pipe/duct and machine system matching, a completely new chapter on ventilation and contamination decay, additional computer model programs, specially printed to facilitate scanning, which cover the full range of fluid flow regimes treated in the text